2002
DOI: 10.1080/01926230213166
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial Myxomatous Change in Harlan Sprague-Dawley Rats (Hsd:S-D) and CD-1 Mice: Its Microscopic Resemblance to Drug-Induced Valvulopathy in Humans

Abstract: A full assessment of all heart valves in rats and mice is often impractical and is usually not performed in routine toxicity studies, largely due to an inevitable inconsistency of histological sampling. The majority of reported heart valve changes involve the examination of a single, semirandom section through the heart and the valvulopathy occurring with age or induced by xenobiotics may have been generally underestimated in mice and rats. Here we describe the incidence and microscopic features of endocardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
1
12
1
Order By: Relevance
“…This change is not associated with increased morbidity or mortality. The low level of reporting of this lesion is considered to be related to inconsistency of sampling in routine toxicity studies (Donnelly 2008, Elangbam et al 2002.…”
Section: Hemolymphoreticular Systemmentioning
confidence: 99%
“…This change is not associated with increased morbidity or mortality. The low level of reporting of this lesion is considered to be related to inconsistency of sampling in routine toxicity studies (Donnelly 2008, Elangbam et al 2002.…”
Section: Hemolymphoreticular Systemmentioning
confidence: 99%
“…90 Nodular or segmental thickening and subendocardial fibromyxoid proliferation, noted in SMV in rats, were similar to those seen in human valvulopathy induced by anorexigens (e.g., fenfluramine and dexfenfluramine), ergot alkaloids (ergotamine and methysergide), and carcinoid syndrome. 25 Anorexigen-induced valvulopathy has been shown to exhibit distinctive microscopic features in humans. McDonald et al 87 demonstrated that anorexigen-exposed valves contain more glycosaminoglycans (GAG) than normal or floppy (also known as myxomatous valvular degeneration) valves.…”
Section: Experimental Models Of Anorexigen-induced Valvulopathymentioning
confidence: 99%
“…Although these historical control data include results from all kinds of dosing routes, such as feed, gavage, inhalation, dermal, drinking water, and vaginal application, some difference(s) might, nonetheless, exist among animals dosed by different routes (data not shown). The spontaneous occurrence of atrial thrombosis, also called auricular thrombosis, has been reported in several animals: rats (MacKenzie and Alison, 1990;Lewis, 1992;Elwell and Mahler, 1999;Ruben et al, 2000;Elangbam et al, 2002), mice (Maita et al, 1988;Hagiwara et al, 1996;Elangbam et al, 2002), cotton rats (Sorden and Watts, 1996), hamsters (Liu and Tilley, 1980;Allen et al, 1985), monkeys (Wood et al, 1978;Kessler and London, 1982;Allen et al, 1985), dogs (Jubb and Kennedy, 1993;Ayers and Jones, 1978), and cats (Jubb and Kennedy, 1993;Ayers and Jones, 1978;Liu and Tilley, 1980). The highest incidence of spontaneous atrial thrombosis reported was 65% in retired breeding BALB/c female mice, probably related to abnormalities of blood coagulation (Hagiwara et al, 1996).…”
Section: Spontaneous Occurrence Of Atrial Thrombosismentioning
confidence: 99%
“…The highest incidence of spontaneous atrial thrombosis reported was 65% in retired breeding BALB/c female mice, probably related to abnormalities of blood coagulation (Hagiwara et al, 1996). Atrial thrombosis has been described in aged animals, including rats and mice, often associated with myocardial lesions, such as degeneration, focal inflammation, mineralization, amyloid deposition, or degenerative myxoid lesions in heart valves (Sorden and Watts, 1996;Ruben et al, 2000;Elangbam et al, 2002). Our historical control data of spontaneously occurring atrial thrombosis might be useful in the evaluation of possible chemical-and drug-related changes in the incidence of this condition, since, in F344 rats and B6C3F1 mice, few explicit reports exist (Ayers and Jones, 1978;Lewis, 1992).…”
Section: Spontaneous Occurrence Of Atrial Thrombosismentioning
confidence: 99%